2016
DOI: 10.1002/2016gl068746
|View full text |Cite
|
Sign up to set email alerts
|

Radiocarbon in dissolved organic carbon of the Atlantic Ocean

Abstract: Marine dissolved organic carbon (DOC) is produced in the surface ocean though its radiocarbon (14C) age in the deep ocean is thousands of years old. Here we show that ≥10% of the DOC in the deep North Atlantic is of postbomb origin and that the 14C age of the prebomb DOC is ≥4900 14C year, ~900 14C year older than previous estimates. We report 14C ages of DOC in the deep South Atlantic that are intermediate between values in the North Atlantic and the Southern Ocean. Finally, we conclude that prebomb DOC 14C a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
62
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(74 citation statements)
references
References 42 publications
12
62
0
Order By: Relevance
“…Oceanic DBC is generally more radiocarbon depleted (Δ 14 C age: 18,000–23,000 yr; Ziolkowski and Druffel ; Coppola and Druffel ) than the bulk DOC (Δ 14 C age: 4000–6000 yr; Druffel et al ). Previous studies observed anomalously high DOC concentrations in the deep Southern Ocean (Druffel and Bauer ; Follett et al ), especially in the Indian Ocean Sector adjacent to Prydz Bay (Bercovici and Hansell ).…”
Section: Discussionmentioning
confidence: 99%
“…Oceanic DBC is generally more radiocarbon depleted (Δ 14 C age: 18,000–23,000 yr; Ziolkowski and Druffel ; Coppola and Druffel ) than the bulk DOC (Δ 14 C age: 4000–6000 yr; Druffel et al ). Previous studies observed anomalously high DOC concentrations in the deep Southern Ocean (Druffel and Bauer ; Follett et al ), especially in the Indian Ocean Sector adjacent to Prydz Bay (Bercovici and Hansell ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, both the DOC latitudinal gradients and modeling approach do not explicitly measure the microbial degradation but infer it indirectly from subsurface spatial gradients in DOC and temperature. However, it can be assumed that these approaches assess the temperature effects on microbial consumption of DOC, as long as abiotic particle-DOC scavenging or solubilization processes are minimal (Druffel et al, 1992(Druffel et al, , 2016.…”
Section: Discussionmentioning
confidence: 99%
“…Δ 14 C versus δ 13 C values of DOC and DIC in samples collected from the YBH and reference site in the South China Sea. Data from the Changjiang and Huanghe (Wang et al, , 2016), Northwest Pacific (Ge et al, ), South Pacific (Druffel & Griffin, ), Pacific (Druffel et al, ), and Atlantic (Druffel et al, ) are shown for comparison. Solid shapes are from this study; unfilled shapes are from previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…DOC in the YBH is also unusually old, as shown by the Δ 14 C‐DOC values, for a shallow high salinity ocean environment which could be attributed to extensive degradation, chemoheterotrophic and/or chemoautotrophic production. In the open ocean, Δ 14 C‐DOC values usually decrease steadily with depth from −200‰ to −400‰ in surface waters to lower values at depths below 1,000 m (−400‰ to −550‰) and then remain relatively constant (Figure S7) (Bauer et al, ; Druffel et al, ; Hansell et al, ). Oceanic profiles of DOC ages thus increase from ~2,000 years in surface waters to ~6,000 years at depth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation